Real Estate Market in Tirana (European Journal of Marketing and Economics, 2018)
The Real Estate Market is the most important branch of Albania economy. This Market is complex and influenced by many factors, we can mention the financial, economic, social and demographic factors. In this paper we are studying the Real Estate Market of Tirana, the development and dynamics of the price of real estate as an integral part of the economy. The data used in this paper are derived from the database of the World Bank, the Institute of Statistics, Bank of Albania Reports, as well as information provided individually on the ground and in various sources. The empirical model analyze the relation between residential price and other independent factors, such as population, gross national income, and the total new dwelling area approved from the government each year. This analyze becomes more complicated by the interference of temporary tendencies during different periods. The econometric model is based on multiple linear regressions, and the analysis extended over a period of 12 years from 2005 to 2016. The price of immovable property can be considered as a major indicator of the business cycle. For this reason, the Real Estate Market investigation is an important part of the analysis of the economic situation of a country.The dependent variable for the purpose of this study will be the selling prices of apartment and residential areas in the capital of Albania, Tirana. Through this paper is analyzed the development and dynamics of the price of real estate as an integral part of the Albanian economy. To accomplish this study, is used the Linear Regression Method.Keyword: Real Estate market, Real Estate price, buble effect, price definition, multiple linear regression method
Keywords: word: Real Estate market, Real Estate price, buble effect, price definition, multiple linear regression method